2007
DOI: 10.1620/tjem.211.151
|View full text |Cite
|
Sign up to set email alerts
|

L-Type Ca2+ Channels in the Enteric Nervous System Mediate Oscillatory Cl- Secretion in Guinea Pig Colon

Abstract: The enteric nervous system regulates epithelial ion and fluid secretion. Our previous study has shown that the low (0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The available evidence suggests that parasympathetic innervations play an important role in the gut motility [ 23 ]. Studies have also indicated that Ach stored in the nonneuronal cells of the gut plays an important role in stimulating the smooth muscle contraction [ 24 ]. Furthermore, the muscarinic receptor innervations can also increase the secretion of mucus from goblet cells.…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence suggests that parasympathetic innervations play an important role in the gut motility [ 23 ]. Studies have also indicated that Ach stored in the nonneuronal cells of the gut plays an important role in stimulating the smooth muscle contraction [ 24 ]. Furthermore, the muscarinic receptor innervations can also increase the secretion of mucus from goblet cells.…”
Section: Discussionmentioning
confidence: 99%
“…These Ach molecules are not stored in the vesicles and are released by organic cation transporters. Their release is considered to produce slow and sustained gut stimulatory action 23 . In an earlier study, the role of calcium has been suggested for the T. chebula mediated stimulation in the gut smooth muscles and the action can be linked to the cholinergic innervations 11 .…”
Section: Discussionmentioning
confidence: 99%